Anti-Inflammatory Properties of MSF, a Lactiplantibacillus plantarum K8 Lysate Fermented with Filipendula glaberrima Extract - Kyeong-Hun Choi; Jonghyo Hong; Ki-Young Kim; Hangeun Kim; Sanghyun Lee; Yunji Lee; Dae-Kyun Chung (Applied Sciences, 2022)
Inflammation plays an important role in the pathogenesis of metabolic syndrome, which increases the risk of heart disease, stroke, type 2 diabetes, atherosclerosis, non-alcoholic fatty liver disease (NAFLD), and obesity. Here, we produced potent anti-inflammatory probiotic lysates, termed MSF (miracle synergistic material made using Filipendula glaberrima), using fermentation with F. glaberrima extracts. MSF inhibited lipopolysaccharide (LPS)-induced tumor necrosis factor (TNF)-α production through down-regulation of c-Jun N-terminal kinase (JNK) signaling. MSF-induced tolerance for TNF-α was mediated by induction of TNF alpha-induced protein 3 (TNFAIP3 or A20). On the other hand, MSF showed a synergistic effect on interleukin (IL)-1β production in LPS-stimulated human monocytic leukemia cell line (THP-1 cells). This synergistic effect of the combination of MSF and LPS might be mediated by nuclear factor kappa B (NF-kB) signaling. The inhibitory effect of TNF-α and synergistic effect of IL-1β due to combining MSF and LPS were significantly higher than those of a combination of L. plantarum K8 lysates and LPS. The MSF and LPS combination showed reduced mouse mortality compared to a combination of L. plantarum K8 lysates and LPS, which correlated with decreased levels of cytokines, hepatic alanine aminotransferase (ALT), and aspartate aminotransferase (AST) in the blood and liver. These results show that probiotic lysates fermented with natural extracts such as F. glaberrima have higher anti-inflammatory efficacy than conventional probiotic lysates or natural extracts.